Metakaolin-lime hydration products and phase stability: - Gameiro, A. (2011)
Metakaolin (MK) is nowadays a well-known pozzolanic material being used in cement-based materials, like mortars and concretes. The reaction of MK with calcium hydroxide yields cementitious products, being the main phases formed at ambient temperature the calcium silicate hydrate (CSH), stratlingite (C2ASH8) and tetra calcium aluminium hydrate (C4AH13). Several discrepancies are presented in literature regarding these phases’ stability, namely the transformation of stratlingite and C4AH13 into hydrogarnet at long term. The consequences of that instability are an increase in the porosity and a loss of compressive strength that can induce a complete material degradation. With the objective of studying the compounds formed in lime/MK pastes and their stability during time, blended pastes were prepared with 50%, 33%, 25%, 17%, 9%, 5% and 0% (wt.%) of MK. These lime/MK pastes were stored at 95% RH and 23 ± 2 ºC. After each predetermined curing time the hydration reaction was stopped subjecting the samples to acetone. TGA-DTA and XRD were used to follow the kinetics of the MK-lime reaction as well the reaction products formed. In this paper the results obtained by the application of microscopic methods, namely by SEM-EDS, are presented and compared with the thermal and mineralogical data.